Physical and chemical characteristics of the active layer and permafrost, Herschel Island, western Arctic Coast, Canada - Kokelj, S.V. (S. V.); Smith, C.A.S. (C. A.S.); Burn, C. (Christopher R.) (Permafrost and Periglacial Processes, 2002)
Physical and geochemical characteristics of near-surface permafrost and the impact of permafrost degradation on soil and water chemistry were investigated at five sites on Herschel Island, Yukon Territory. The distribution of soluble cations, moisture and organic matter content in turbic cryosols from undisturbed terrain indicated a thaw unconformity 50 to 80 cm below the base of the present active layer. Palaeoactive-layer depth, estimated at between 90 and 100 cm, is less than at comparable sites in the Mackenzie Delta area. The difference may be due to the comparative proximity of Herschel Island to the Beaufort Sea coastline in the early Holocene. Soluble cations in permafrost and the active layer of static cryosols at recently disturbed sites were two orders of magnitude higher than in the active layer at undisturbed sites. Na+ was the dominant cation in undisturbed permafrost, recently disturbed ground, and surface runoff derived from disturbed areas. Although degradation of permafrost following terrain disturbance has resulted in surface salinization, a condition detrimental to vegetation growth, leaching of soluble salts from disturbed areas has occurred over time. These processes have produced a range of soil conditions that contribute to the floristic diversity of Herschel Island. Copyright